Foreign Direct Investment Inflows and Intellectual Property Rights: A Further Empirical Look [Siew Mei CHAN & Tuck Cheong TANG] - Chan, S.M.; Tang, T.C. (2016)

(untitled)
This study documents a richer empirical look on the role of intellectual property rights (IPRs) on FDI inflows by considering global data including different income groups (i.e. high, middle, and low income groups classified by World Bank). It also looks at the (short-run) impact of the TRIPS (Trade-Related Aspects of Intellectual Property Rights) agreement which imposed during the Uruguay Round in 1995. The empirical model relates FDI inflows to IPRs, controlled by a set of known variables - GDP per capital, trade openness, real exchange rate, and real interest rate. The empirical computation covers panel data of between 35 and 100 countries for the period 1980-2014. The empirical results suggest cointegration (long-run relation) between IPRs and FDI inflow globally, regardless of different income groups. Their impact is estimated between 0.023 and 0.043, but insignificant in the short-run. Causality tests further support the role of IPRs on FDI. Various transmission channels have been identified, in particularly for low income countries. Positive finding is documented for the countries joining the TRIPS agreement. This study enlightens policymakers about the policy on creating a conducive and sustainable environment for IPRs in order to encourage FDI inflows to their countries. A small open economy in Asia - Malaysia is being considered as case study for Asian context.